Impact of Remittances on Economic Growth in Africa: An Econometric Analysis - Amir, Md. Zobayer Bin; Amir, Md. Khaled Bin (International Journal of Economics and Financial Issues, 2024)
We propose that natural disasters enable frequent and severe market manipulation. Remittances have impact on economic growth of African nations. We tested this proposition by employing panel data from 42 African nations from 2001 to 2020.The fixed effect model is representative of all models used in this study. The unemployment rate (UR) is used as an instrumental variable in the Generalized Momentum Method (GMM) estimation to reduce the endogeneity problem. This study suggests that remittances have a significant positive impact on the economic growth of African nations.